2017
DOI: 10.1136/heartjnl-2017-311448
|View full text |Cite
|
Sign up to set email alerts
|

Reactive oxygen species signalling in the diabetic heart: emerging prospect for therapeutic targeting

Abstract: Despite being first described 45 years ago, the existence of a distinct diabetic cardiomyopathy remains controversial. Nonetheless, it is widely accepted that the diabetic heart undergoes characteristic structural and functional changes in the absence of ischaemia and hypertension, which are independently linked to heart failure progression and are likely to underlie enhanced susceptibility to stress. A prominent feature is marked collagen accumulation linked with inflammation and extensive extracellular matri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
106
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(110 citation statements)
references
References 53 publications
4
106
0
Order By: Relevance
“…The dynamic balance of mitochondrial fusion and fission is essential for maintaining cardiomyocyte function, including energy production and cell survival . Emerging data have indicated that both mitochondrial dysfunction and mitochondrial ROS are implicated in the pathogenesis of DCM, whereas the mechanisms underlying mitochondrial damage in DCM are still largely unclear. The incidence of diabetes is unpredictable, therefore it would be more meaningful to mimic clinical scenario if the treatment are given after one period since the onset of diabetes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic balance of mitochondrial fusion and fission is essential for maintaining cardiomyocyte function, including energy production and cell survival . Emerging data have indicated that both mitochondrial dysfunction and mitochondrial ROS are implicated in the pathogenesis of DCM, whereas the mechanisms underlying mitochondrial damage in DCM are still largely unclear. The incidence of diabetes is unpredictable, therefore it would be more meaningful to mimic clinical scenario if the treatment are given after one period since the onset of diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetic cardiomyopathy is characterized by abnormal cardiac structure and function that are independent of coronary artery disease or hypertension . Although excessive production of reactive oxygen species (ROS) and increased apoptotic cell death have been proposed as potential contributed factors in the pathogenesis of DCM, accumulating evidence demonstrates the imbalanced mitochondrial fusion/fission dynamics is an initial cause for these events . Excessive mitochondrial fission has been associated with an overproduction of ROS and increased apoptotic cell death in diabetic hearts.…”
Section: Introductionmentioning
confidence: 99%
“…Lok et al reported that NRG-1 can decrease human brain endothelial cells death after oxidative injury with H 2 O 2 [29]. Oxidative stress caused by mitochondrial superoxide overproduction in endothelial cells is the major mechanism in the development of vascular complications in diabetes [30, 31]. Previous study reported that NRG-1 can alleviate oxidative and endoplasmic reticulum stress in heart [32].…”
Section: Discussionmentioning
confidence: 99%
“…Cardiomyocytes are particularly susceptible to diabetic insults caused by dysfunctional mitochondria 13, 14. Mitochondria that are damaged during diabetic stress can produce reactive oxygen species (ROS) and release death‐inducing factors, thus augmenting cardiomyocyte injury 14, 15, 16…”
Section: Introductionmentioning
confidence: 99%